O Pewnym Prawie Pełzania - Klepaczko, J. (Engineering Transactions, 1965)
The paper contains a discussion of the creep law of metals proposed by Andrade. The discussion is based on the law of E. A. DAVIS [6] generalized to the case of a variable temperature U = B(T)EM(T) EN(T), where B(T), m (T), n (T) denote the plastic modulus, the strain hardening exponent and the strain-rate sensitivity, respectively. These quantities depend all on the absolute temperature. This law is valid for technically pure polycrystalline metals of rectangular plane-centric network, such as Al, Cu and Pb.As a result of discussion it is found that for the first stage of creep Andrade's law is valid in a definite region of elevated temperatures, For aluminium and copper these regions are located near the temperature 6 A R 0,65 in the homologous scale.